2011
DOI: 10.1038/jp.2010.208
|View full text |Cite|
|
Sign up to set email alerts
|

A review of alternatives to di (2-ethylhexyl) phthalate-containing medical devices in the neonatal intensive care unit

Abstract: Objective To conduct an extensive literature and toxicological database review on substitute compounds and available alternative medical products to replace polyvinyl chloride (PVC) and/or di(2-ethylhexyl) phthalate (DEHP), and conduct a DEHP-medical inventory analysis at a large metropolitan neonatal intensive care unit (NICU). Study Design A systematic search for DEHP-free alternative products was performed using online databases. An informal audit of a large metropolitan NICU was undertaken in 2005 and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 57 publications
1
45
0
Order By: Relevance
“…However, the replacement of DEHP poses both technical challenges and there exist data gaps on the safety of these alternatives (Dumont et al, 2012;Lagerberg et al, 2015;Simmchen et al, 2012;Van Vliet et al, 2011). Considering the known deleterious effects of these EDCs in the general population and the in vitro effects described at the reported levels, further research into the clinical effects of EDCs leaching from medical devices in ICU patients and their possible substitutes should be performed.…”
Section: Tablementioning
confidence: 97%
“…However, the replacement of DEHP poses both technical challenges and there exist data gaps on the safety of these alternatives (Dumont et al, 2012;Lagerberg et al, 2015;Simmchen et al, 2012;Van Vliet et al, 2011). Considering the known deleterious effects of these EDCs in the general population and the in vitro effects described at the reported levels, further research into the clinical effects of EDCs leaching from medical devices in ICU patients and their possible substitutes should be performed.…”
Section: Tablementioning
confidence: 97%
“…However, the toxicity of DEHP and congener phthalates has been and remains a topic of public concern [2,3]. The exposure of transfusion patients to the DEHP that leaches out of PVC blood bags during component storage has been widely discussed [4,5], with particular concern for pediatric recipients [6,7]. For red blood cell (RBC) components, replacing DEHP by a non-phthalate PVC plasticizer is challenged by the membrane protective effect that DEHP exerts on RBCs ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…None of these plasticizers are devoid of potential health hazards but DINCH shows the lowest reproductive and developmental toxicity [6], which is also a DEHP-associated risk of concern for pediatric recipients. It has been previously shown that RBCs can be stored satisfactorily in BTHC-plasticized bags [12], despite inferior protection against hemolysis and vesiculation (assessed as the cell-free, membrane-bound protein concentration during storage) compared to DEHP [13].…”
Section: Introductionmentioning
confidence: 99%
“…The appeal to these alternatives is two-fold; first and foremost, most of these chemicals appear to be less toxic compared with DEHP or BPA, and second, these alternatives can be marketed as “phthalate-free” which appeals to consumers. Unsurprisingly, all of these plastic additives have their own individual drawbacks 180186 , including: higher price, less efficiency, significant leaching, insufficient purity, and adverse health effects. The major drawback to these alternative products is that they are relatively untested and the toxicological data on these substitutes is extremely limited.…”
Section: Questions Remainingmentioning
confidence: 99%